A Variable Stiffness Actuator Module With Favorable Mass Distribution for a Bio-inspired Biped Robot - Rodriguez-Cianca, David; Weckx, Maarten; Jimenez-Fabian, Rene; Torricelli, Diego; Gonzalez-Vargas, Jose; Sanchez-Villamañan, M.Carmen; Sartori, Massimo; Berns, Karsten; Vanderborght, Bram; Pons, J. Luis; Lefeber, Dirk (Frontiers in Neurorobotics, 2019)
Achieving human-like locomotion with humanoid platforms often requires the use of variable stiffness actuators (VSAs) in multi-degree-of-freedom robotic joints. VSAs possess 2 motors for the control of both stiffness and equilibrium position. Hence, they add mass and mechanical complexity to the design of humanoids. Mass distribution of the legs is an important design parameter, because it can have detrimental effects on the cost of transport. This work presents a novel VSA module, designed to be implemented in a bio-inspired humanoid robot, Binocchio, that houses all components on the same side of the actuated joint. This feature allowed to place the actuator’s mass to more proximal locations with respect to the actuated joint instead of concentrating it at the joint level, creating a more favourable mass distribution in the humanoid. Besides, it also facilitated its usage in joints with centralized multi-degree of freedom (DoF) joints instead of cascading single DoF modules. The design of the VSA module is presented, including its integration in the multi-DoFs joints of Binocchio. Experiments validated the static characteristics of the VSA module to accurately estimate the output torque and stiffness. The dynamic responses of the driving and stiffening mechanisms are shown. Finally, experiments show the ability of the actuation system to replicate the envisioned human-like kinematic, torque and stiffness profiles for Binocchio.